Developing quality healthcare software using quality function deployment: a case study based on Sultan Qaboos University Hospital - Ahmed, Mohiuddin; Islam, Rafikul; Al-wahaibi, Salim Khloof (Inderscience Enterprises Ltd., 2006)
Development of software is one of the most expensive projects undertaken in practice. Traditionally, the rate of failure in software development projects is higher compared to other kinds of projects. This is partly due to the failure in determining software users’ requirements. By using Quality Function Deployment (QFD), this research focuses on identification and prioritization of users’ requirements in the context of developing quality health-care software system for Sultan Qaboos University Hospital (SQUH) in Oman. A total of 95 staff working at eight departments of SQUH were contacted and they were requested to provide their requirements in using hospital information systems. Analytic Hierarchy Process has been integrated with QFD for prioritizing those user requirements. Then, in consultation with a number of software engineers, a list consisting of 30 technical requirements was generated. These requirements are divided into seven categories and all of them are purported to satisfy the user requirements. At the end of QFD exercise, continuous mirror backup from ‘backup’ category, multi-level access from the ‘security and confidentiality’ category, and linkage to databases from ‘application’ category emerge as technical requirements that possess higher weights. These technical requirements should receive considerable attention at the time of designing the health-care software system for SQUH.